Growth, plant water relations, photosynthesis rate and accumulation of proline in young carambola plants in relation to water stress - Ismail, Mohd Razi; Burrage, S.W.; Tarmizi, H.; Aziz, M.A. (1994)
The effects of water availability on growth, water relations and related plant physiological and biochemical activities of young starfruit (Averrhoa carambola) plants were investigated. Plant vegetative growth was inhibited with reduced water availability. Leaf water potential, relative water content and canopy transpiration were reduced with increasing soil water stress. Leaf photosynthesis rate was reduced when stomatal resistance exceeded 3.5 s cm-1. Proline was 8.1, 13.2 and 20.5 times higher in the leaves of plants that were stressed for 1, 2 and 4 weeks, respectively, compared with the control. Photon flux density higher than 1000 μmol m-2 s-1 reduced the leaf photosynthetic rate of stressed and unstressed plants. © 1994.